Peningkatan Minat Belajar Sejarah Peserta Didik Melalui Media Pembelajaran Blooket di Kelas XI.2 SMAN 1 Darma - Chika Fadhilla Khairunnisa; Oka Agus Kurniawan Shavab; Yulia Sofiani (Jurnal Artefak, 2025)
This study aims to analyze the effect of using Blooket as a learning medium on students’ interest in history learning in class XI.2 of SMAN 1 Darma. The research was motivated by the low learning interest caused by monotonous media use. A quantitative approach with a quasi-experimental method using a non-equivalent control group design was applied. The sample consisted of 64 students, with 32 in the experimental class (XI.2) and 32 in the control class (XI.5), selected through purposive sampling. Data were collected through a validated and reliable Likert scale questionnaire and analyzed using an independent sample t-test with SPSS. The results indicated a significant difference between the experimental and control groups, with a significance value of 0.001 < 0.05. These findings confirm that Blooket positively influences students’ interest in learning history. Thus, Blooket can serve as an effective interactive learning medium to enhance student engagement in history education.